Identifying Alternative Revenue Streams for Independent Musicians - Nolan, John Henry (East Carolina University, 2017)
In the modern music industry, there has been a number of changes to the shape of the business as a whole that are affecting smaller, independent musicians in a negative way. These artists and groups are at a disadvantage because of the lack of financial resources available to them and the already limited means they have to create, distribute, and perform their music. However, after a review of a survey distributed to consumers, it is evident that there are a number of opportunities at these musician’s live performances that could be utilized to increase revenue.
Keywords: Music Industry, Independent Musicians, Revenue